The EGA Negotiations: why they are important, why they are stalled, and challenges ahead - Jaime de Melo; Jean-Marc Solleder (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
Decade-long negotiations on the reduction of tariffs on Environmental Goods (EGs) at the Doha Round using a list approach to define EGs, failed to produce an agreement. In July 2014, 14 countries entered plurilateral negotiations under the ambit of the WTO. If successful, the resulting Environmental Goods Agreement (EGA) would have eliminated tariffs on a list of EGs. These negotiations broke down in December 2016. The chapter documents this episode and the mercantilistic behavior of negotiators that prevented agreement on an extended list of EGs, a requirement to conclude a meaningful outcome for the environment.A conclusion of the EGA negotiations under the current narrow agenda focusing only on tariffs could help build trust to go further but would be insufficient to help mitigate climate change, even if a 'critical mass' were to be reached allowing extension of the tariff reductions to all WTO members. This is because average tariffs for the negotiating group are too low (1.5 percent). Extending the agenda to include Non-Tariff Barriers (NTBs) and Environmental Services (ESs) remains the acid test for an EGA to address meaningfully the climate change challenge. Reaching agreement on how to tackle NTBs and ESs will require delegating negotiating authority to 'independent' scientific experts and probably modifying WTO rules.Aligning the trade and climate regimes will call for transformational changes in the WTO contract to take into account transnational externalities and public goods. This would amount to a shift from the present 'negative contract' where countries are free to choose their policies so long as they do not discriminate between domestic and imported goods to a 'positive contract' where WTO members have to pursue similar climate-friendly policies. This paper draws and summarizes Melo and Solleder (2018b) that covers the broader role required of a successful EGA to mitigate climate change. The authors thank the French government for financial support under ANR-LABX-14-01.
Keywords: 330